Occupational injuries associated with safety climate among ceramic industry workers in Iran - Saeed Shojaee Barjoee; Vladimir Rodionov; Neda Rezaei (Scientific Reports)
Abstract This study conducted a descriptive analysis of non-fatal physical injuries and safety climate in the Iranian ceramic industry from 2020 to 2023. The following risk factors (independent variables) were examined in this study: age, gender, work experience, work shift of workers, time of occurrence of injury, injured body part, severity of injury, and outcome of injury. Occupational injury prevalence rates as dependent variables were used to analyze the injury data. The safety climate was evaluated using the NOSACQ-50 questionnaire. Results showed a rising trend in the prevalence rate of occupational injuries from 2020 to 2023. The men in the age group of 38–43 years’ experience the most occupational injuries. The highest frequency of injuries happened in the morning shift at 10 o’clock, and workers with less than one year of experience were most affected. Fingers were the most injured part, and trauma was the most common outcome. The highest injury rates occurred in squaring, cutting, and packaging workplaces. The findings also indicated that workers generally have a poor level of safety climate (the mean safety climate score: 2.88), which highlights their excessive risk-taking behavior and lack of safety prioritization. Compared to the non-injury groups, the injured groups’ safety climate score was lower. This study suggests that the ceramics industry may be able to lower occupational injuries by improving workplace safety climate dimensions.